Long term outcome of prophylaxis for febrile convulsions. Issue 1 (January 1996) - Knudsen, F U; Paerregaard, A; Andersen, R; Andresen, J
Abstract : A cohort of 289 children with febrile convulsions who had been randomised in early childhood to either intermittent prophylaxis (diazepam at fever) or no prophylaxis (diazepam at seizures) was followed up 12 years later. The study focused on the occurrence of epilepsy and on neurological, motor, intellectual, cognitive, and scholastic achievements in the cohort. At follow up the two groups were of almost identical age (14.0 v 14.1 years), body weight (58.2 v 57.2 kg), height (168.2 v 167.7 cm), and head circumference (55.9 v 56.2 cm). The occurrence of epilepsy (0.7% v 0.8%), neurological examination, fine and gross motor development on the Stott motor test, intellectual performance on the Wechsler intelligence scale for children verbal IQ (105 v 105), performance IQ (114 v 111), and full scale IQ (110 v 108), cognitive abilities on a neuropsychological test battery, including short and long term, auditory and visual memory, visuomotor tempo, computer reaction time, reading test, and scholastic achievement were also very similar. Children with simple and complex febrile convulsions had the same benign outcome. The long term prognosis in terms of subsequent epilepsy, neurological, motor, intellectual, cognitive, and scholastic ability was not influenced by the type of treatment applied in early childhood. Preventing new febrile convulsions appears no better in the long run than abbreviating them.